Induced Resistance in Fruit and Vegetable Enhancing Host Defence to Curve Post-harvest Diseases - , E K Naik, Marimuthu Elangovan, Sanjay Kumar, Priyanka Kumari Meena; Shivam, Mansi Nautiyal, T. Sivasankari Devi, K. Sathya (Archives of Current Research International, 2024)
Induced resistance (IR) is an emerging, environmentally friendly strategy to manage post-harvest diseases in fruits and vegetables by enhancing the plant’s innate immune system. This approach leverages the plant's natural defense mechanisms, including the activation of defense-related enzymes like chitinases, glucanases, and peroxidases, accumulation of secondary metabolites such as phytoalexins and phenolics, and the strengthening of cell walls to prevent pathogen invasion. Additionally, the production of reactive oxygen species (ROS) plays a crucial role in both signaling and direct pathogen inhibition. Despite its potential, the effectiveness of IR varies across different crops and pathogens, and its success is heavily influenced by environmental factors, such as humidity, temperature, and light. There are also concerns regarding possible trade-offs, such as reduced yield or changes in fruit quality due to the diversion of energy towards defense responses. However, the integration of IR with other disease management strategies, including the use of biological control agents and conventional fungicides, has shown promising results in reducing post-harvest losses. Case studies in fruits like apples, tomatoes, and citrus, as well as vegetables like potatoes and peppers, demonstrate the practical applications of IR in commercial agriculture. Advances in genetic engineering are opening new pathways for enhancing IR by manipulating key genes involved in defense pathways, while new formulations and precision agriculture technologies offer greater control and efficiency in IR applications. These innovations, along with optimized post-harvest handling and storage practices, hold the potential to make IR a more reliable and sustainable solution for managing post-harvest diseases. However, ongoing research is necessary to address the variability in effectiveness and to explore long-term sustainability, especially as pathogens evolve and environmental conditions change. Induced resistance, when integrated with a comprehensive disease management approach, offers a significant step forward in reducing post-harvest losses and improving food security globally.